dane są wyrażenia algebraiczne f i g wyznacz f+g oraz f-g​

Dane Są Wyrażenia Algebraiczne F I G Wyznacz Fg Oraz Fg class=

Odpowiedź :

Odpowiedź:

d) F + G = (2x - y) + ( - (x - 2y)) = 2x - y + (- x + 2y) = 2x - y - x + 2y = x + y

   F + G = (2x - y) - ( - (x - 2y)) = 2x - y - (- x + 2y) = 2x - y + x - 2y = 3x - 3y =

   = 3(x -y)

e) F + G = - (2a - b) + 2a + b = - 2a + b + 2a + b = 2b

   F - G = - (2a - b) - (2a + b) = - 2a + b - 2a - b = - 4a

f) F + G = - (a - b) + (- (a + b) = - a + b + ( - a + b) = - a + b - a + b = - 2a + 2b =

   = - 2(a - b)

   F - G = - (a - b) - (- (a + b) = -a + b - ( -a - b) = - a + b + a + b = - 2a + 2b =

   = - 2(a - b)